Harnessing the genomic diversity of Pseudomonas strains against lettuce bacterial pathogens - Zboralski, Antoine; Biessy, Adrien; Ciotola, Marie; Cadieux, Mélanie; Albert, Daphné; Blom, Jochen; Filion, Martin (Frontiers in Microbiology, 2022)
Lettuce is a major vegetable crop worldwide that is affected by numerous bacterial pathogens, including Xanthomonas hortorum pv. vitians, Pseudomonas cichorii, and Pectobacterium carotovorum. Control methods are scarce and not always effective. To develop new and sustainable approaches to contain these pathogens, we screened more than 1,200 plant-associated Pseudomonas strains retrieved from agricultural soils for their in vitro antagonistic capabilities against the three bacterial pathogens under study. Thirty-five Pseudomonas strains significantly inhibited some or all three pathogens. Their genomes were fully sequenced and annotated. These strains belong to the P. fluorescens and P. putida phylogenomic groups and are distributed in at least 27 species, including 15 validly described species. They harbor numerous genes and clusters of genes known to be involved in plant-bacteria interactions, microbial competition, and biocontrol. Strains in the P. putida group displayed on average better inhibition abilities than strains in the P. fluorescens group. They carry genes and biosynthetic clusters mostly absent in the latter strains that are involved in the production of secondary metabolites such as 7-hydroxytropolone, putisolvins, pyochelin, and xantholysin-like and pseudomonine-like compounds. The presence of genes involved in the biosynthesis of type VI secretion systems, tailocins, and hydrogen cyanide also positively correlated with the strains’ overall inhibition abilities observed against the three pathogens. These results show promise for the development of biocontrol products against lettuce bacterial pathogens, provide insights on some of the potential biocontrol mechanisms involved, and contribute to public Pseudomonas genome databases, including quality genome sequences on some poorly represented species.